2014
DOI: 10.1136/annrheumdis-2013-205020
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association and functional studies identify a role forIGFBP3in hip osteoarthritis

Abstract: Objectives To identify genetic associations with hip osteoarthritis (HOA), we performed a meta-analysis of genome-wide association studies (GWAS) of HOA. Methods The GWAS meta-analysis included approximately 2.5 million imputed HapMap single nucleotide polymorphisms (SNPs). HOA cases and controls defined radiographically and by total hip replacement were selected from the Osteoporotic Fractures in Men (MrOS) Study and the Study of Osteoporotic Fractures (SOF) (654 cases and 4697 controls, combined). Replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Some of these genes are involved in well‐described IGF regulatory or signaling pathways (such as IGFBP3 and IGFALS ) (Deal et al ., 2001; Gu et al ., 2010; Schumacher et al ., 2010) and are believed to influence traits that are also associated with concentrations or bioactivity of IGFs (e.g., FOXO3 locus associated with longevity (Willcox et al ., 2008) and IGFBP3 locus associated with hip osteoarthritis (Evans et al ., 2015)). To identify additional genetic variants with smaller effect sizes and enable sex specific analyses, we expanded our GWAS meta‐analysis to include up to a total of 30 884 individuals of European ancestry from 21 studies with measured circulating concentrations of IGF‐I and IGFBP‐3.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these genes are involved in well‐described IGF regulatory or signaling pathways (such as IGFBP3 and IGFALS ) (Deal et al ., 2001; Gu et al ., 2010; Schumacher et al ., 2010) and are believed to influence traits that are also associated with concentrations or bioactivity of IGFs (e.g., FOXO3 locus associated with longevity (Willcox et al ., 2008) and IGFBP3 locus associated with hip osteoarthritis (Evans et al ., 2015)). To identify additional genetic variants with smaller effect sizes and enable sex specific analyses, we expanded our GWAS meta‐analysis to include up to a total of 30 884 individuals of European ancestry from 21 studies with measured circulating concentrations of IGF‐I and IGFBP‐3.…”
Section: Introductionmentioning
confidence: 99%
“…By combining reported genetic OA signals with AI SNPs that alter transcription of articular cartilage genes in ‐ cis , we also had the opportunity to address functionality of OA risk alleles. For example, the A allele of rs788748, located upstream of IGFBP3 , is associated with lower odds of hip OA . Given that this SNP is not located in an exon, we assessed its potential revelance to AI through rs6670 double heterozygotes, which revealed that the protective rs788748 A allele marks lower expression of IGFBP3 compared to the G allele.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, IGFBP3‐induced hBMSC migration coincided with the activation of CCR2 and CCR2 inhibitors completely blocked the IGFBP3‐induced MSC migration, indicating that IGFBP3 promoted hBMSC migration through a CCR2‐dependent mechanism (Figures and ). On the other hand, genome‐wide association and functional studies have shown that IGFBP3 overexpression induced cartilage catabolism and osteogenic differentiation in hip osteoarthritis (Evans et al, ). Transcriptome analysis of homing cells showed that the hUCMSC‐ECM significantly increased the expressions of 7 promigratory genes, including TβRI and CCR2 in vivo (Figure a).…”
Section: Discussionmentioning
confidence: 99%